The Mediational Role of Desire for Cultural Tightness on Concern With COVID-19 and Perceived Self-Control - Mula, Silvana; Di Santo, Daniela; Gelfand, Michele J.; Cabras, Cristina; Pierro, Antonio (Frontiers in Psychology, 2021)
When ecological threats are more severe or prevalent, societies are more likely to tighten their social norms and punishments. Moreover, when people follow clear and tight rules, they are more prone to regulate their behavior (i.e., self-control) in order to avoid punishment. Therefore, we examined the mediating role of people’s endorsement of cultural tightness (i.e., support and desire) on the relationship between concern with COVID-19 threat and personal self-control. Our hypothesis was tested through a mediation model in two studies with a sample of (N=315, 77.1% females, Mage=23.71) university students (Study 1) and with a heterogeneous sample of (N=239, 65.7% females, Mage=36.55) participants (Study 2). Empirical support for the proposed model was found in both studies. Implications of this research will be discussed. The main implication is related to the possibility that people’s desire for strong norms to cope with the COVID-19 threat could promote greater self-regulated preventive behavior in order to protect their health.